Exploring Entrepreneurship Education, SME Growth, Leadership, And Governance - Tursinah Anggendari; Sri Utami Nurhasanah (Universitas 45 Surabaya, 2023)
This research aims to elucidate the intricate relationships among entrepreneurship education, small and medium enterprise (SME) development, leadership, and corporate governance to combat unemployment and poverty. Employing a mixed-method approach, the study will utilize purposive sampling to select participants from diverse sectors. Data analysis will involve thematic coding and content analysis to uncover emergent patterns and themes. The research endeavors to unveil how effective entrepreneurship education, coupled with sound leadership and good corporate governance practices, can foster SME growth, thereby mitigating unemployment and poverty. Preliminary findings suggest that a holistic approach integrating these elements is imperative for sustainable socio-economic development.